2010
DOI: 10.1021/cm903688z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects on Band Gap-Narrowing in Titania by Codoping from First-Principles Calculations

Abstract: The large intrinsic band gap in TiO 2 has hindered severely its potential application for visible-light irradiation. In this study, we have used a passivated approach to modify the band edges of anatase-TiO 2 by codoping of X (N, C) with transition metals (TM=W, Re, Os) to extend the absorption edge to longer visible-light wavelengths. It was found that all the codoped systems can narrow the band gap significantly; in particular, (N+W)-codoped systems could serve as remarkably better photocatalysts with both n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
103
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 36 publications
12
103
0
Order By: Relevance
“…The calculated band gap of pure anatase TiO 2 is 2.95 eV (Fig. 3a), which is consistent with the reported results [24,32]. However, the Fermi level in the F-doped case shifts from the top of valence band to the bottom of conduction band, which is a typical characteristic of the n-type doping.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The calculated band gap of pure anatase TiO 2 is 2.95 eV (Fig. 3a), which is consistent with the reported results [24,32]. However, the Fermi level in the F-doped case shifts from the top of valence band to the bottom of conduction band, which is a typical characteristic of the n-type doping.…”
Section: Resultssupporting
confidence: 90%
“…A series of U values was tested for the Ti 3d orbitals. The band gap for pure TiO 2 was calculated to be 2.95 eV when the U was set to 7.0 eV, in agreement with previous GGA + U theoretical results [24,32]. We, therefore, selected the U values as 7.0 eV to address the Ti 3d orbital electrons.…”
Section: Computational Detailssupporting
confidence: 76%
See 1 more Smart Citation
“…To account for strongly correlated interactions of the d shells, the DFT+U method was used to calculate the electronic properties, and on-site effective U (U =U'-J) parameters, introduced by Dudarev et al [23], were applied to Ti 3d and Cr 3d electrons. Our previous work has shown that this method affords a good description for both geometric and electronic structures [7][8][9], and this has also been found by Yang et al [5].…”
Section: Computational Methodologysupporting
confidence: 75%
“…To extend its photon absorption edge to the visible-light region, it is necessary to improve the photocatalytic efficiency, and many experiments have been performed to dope impurity atoms into the TiO 2 lattice in an attempt to narrow the band gap and to improve the efficiency. Both mono-and co-doping by metal and non-metal elements have been reported [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%